2021
DOI: 10.1111/pbi.13638
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of flavour‐related linalool is regulated by PpbHLH1 and associated with changes in DNA methylation during peach fruit ripening

Abstract: Linalool is one of the common flavour-related volatiles across the plant kingdom and plays an essential role in determining consumer liking of plant foods. Although great process has been made in identifying terpene synthase (TPS) genes associated with linalool synthesis, much less is known about regulation of this pathway. We initiated study by identifying PpTPS3 encoding protein catalysing enantiomer (S)-(+)-linalool synthesis, which is a major linalool component (~70%) observed in ripe peach fruit. Overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…As a result, hundreds of complete TPSs that contained both domains were identified. A recent study used this similar approach to detect TPSs in peach [2], and it detected 38 full-length TPSs with both domains; another study detected cultivated apple contained 55 putative TPS genes [4], the similar amount of TPSs as our results indicates the approach used in our study is reliable. For each Rosoideae species, we found that a certain ratio (64.29-0%) of putative TPSs was composed of both domains.…”
Section: Identification Of Tps Family Members In Rosaceaesupporting
confidence: 73%
See 2 more Smart Citations
“…As a result, hundreds of complete TPSs that contained both domains were identified. A recent study used this similar approach to detect TPSs in peach [2], and it detected 38 full-length TPSs with both domains; another study detected cultivated apple contained 55 putative TPS genes [4], the similar amount of TPSs as our results indicates the approach used in our study is reliable. For each Rosoideae species, we found that a certain ratio (64.29-0%) of putative TPSs was composed of both domains.…”
Section: Identification Of Tps Family Members In Rosaceaesupporting
confidence: 73%
“…On the whole, the above finding indicated that TPSs in Rosaceae also underwent extensive expression differentiation after the split of sister lineages and gene duplication. thases; their product s-linalool is assumed to be an important flavor component in P. persica [2]. On the whole, the above finding indicated that TPSs in Rosaceae also underwent extensive expression differentiation after the split of sister lineages and gene duplication.…”
Section: Tissue-specific Expression Of Tpss In Rosaceaementioning
confidence: 85%
See 1 more Smart Citation
“…Linalool, an acyclic monoterpene that also imparts sweet, floral, alcoholic note, and terpene synthases (TPSs), is the vital enzyme involved in the formation of linalool [ 49 ]. Wei et al identified that overexpression PpTPS3 led to the accumulation of linalool while gene silencing led to 66.5% linalool reduction in peach [ 50 ]. In addition, transcription factor PpbHLH1 activated PpTPS3 by directly binding to its promoter region, validating its role in linalool accumulation [ 50 ].…”
Section: Peach Ripening-related Changesmentioning
confidence: 99%
“…Wei et al identified that overexpression PpTPS3 led to the accumulation of linalool while gene silencing led to 66.5% linalool reduction in peach [ 50 ]. In addition, transcription factor PpbHLH1 activated PpTPS3 by directly binding to its promoter region, validating its role in linalool accumulation [ 50 ]. Another study showed that UV-B irradiation reduced linalool production through modulation of terpene synthase gene ( PpTPS1 ) [ 51 ].…”
Section: Peach Ripening-related Changesmentioning
confidence: 99%